2003
DOI: 10.1016/s0896-6273(03)00064-3
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Direction Selectivity of Synaptic Inputs in Visual Cortical Neurons

Abstract: This intracellular study investigates synaptic mechanisms of orientation and direction selectivity in cat area 17. Visually evoked inhibition was analyzed in 88 cells by detecting spike suppression, hyperpolarization, and reduction of trial-to-trial variability of membrane potential. In 25 of these cells, inhibition visibility was enhanced by depolarization and spike inactivation and by direct measurement of synaptic conductances. We conclude that excitatory and inhibitory inputs share the tuning preference of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
367
4
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 342 publications
(430 citation statements)
references
References 66 publications
56
367
4
3
Order By: Relevance
“…Other studies have failed to find substantial evidence for orthogonal tuning of inhibition [1,23,46]. Recently, in a comprehensive study, Monier et al [44] have convincingly demonstrated that indeed the orientation tuning of inhibitory synaptic inputs shows substantial variability across the population. While the majority of neurons receive inhibition that peaks at their preferred orientation, a substantial minority receive inhibitory inputs that are orthogonal or oblique to their preferred orientation.…”
Section: Diversity In Subthreshold Tuningmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies have failed to find substantial evidence for orthogonal tuning of inhibition [1,23,46]. Recently, in a comprehensive study, Monier et al [44] have convincingly demonstrated that indeed the orientation tuning of inhibitory synaptic inputs shows substantial variability across the population. While the majority of neurons receive inhibition that peaks at their preferred orientation, a substantial minority receive inhibitory inputs that are orthogonal or oblique to their preferred orientation.…”
Section: Diversity In Subthreshold Tuningmentioning
confidence: 99%
“…There is now substantial experimental support for some of the aspects of this model ( [24,37,50]; see [25] for a recent review). However, there are also numerous features of orientation tuning that this model cannot explain ( [14,21,44,52]; see [63,65] for a review). Several computational models have proposed alternate schemes, based primarily on recurrent amplification of inputs to cortex, that can largely explain the experimental data without recourse to a strict arrangement of thalamocortical projections required by the feedforward model [7,17,64].…”
Section: Orientation Tuning In Primary Visual Cortexmentioning
confidence: 99%
See 3 more Smart Citations